2013
DOI: 10.1159/000347194
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis: Current and Future Treatment Strategies

Abstract: Since the incidence of inflammatory bowel diseases including ulcerative colitis is continuously increasing worldwide, there is a strong need for effective treatment strategies. However, there is no therapy allowing for healing ulcerative colitis; consequently, the available medications will have to be applied at their best. The preferred option for mild pan- or left-sided colitis is still mesalazine. One can only emphasize that the formulations allowing for once daily dosing are not only equally effective, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…A systematic review by Molodecky et al [1] found that highest prevalence was found in Europe (UC, 505 per 100,000 persons) and North America (UC, 249 per 100,000 persons). The therapy of choice for colitis is mesalazine and sulfasalazine is used for maintenance [2]. However, the safety of sulfasalazine decays in patients with known tolerance, and it can cause unwanted effects on male infertility [3].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review by Molodecky et al [1] found that highest prevalence was found in Europe (UC, 505 per 100,000 persons) and North America (UC, 249 per 100,000 persons). The therapy of choice for colitis is mesalazine and sulfasalazine is used for maintenance [2]. However, the safety of sulfasalazine decays in patients with known tolerance, and it can cause unwanted effects on male infertility [3].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical (IHC) analysis was performed on CT26 tumor allografts, and colon tissue samples as described previously1, 7. Briefly, unstained 5 μm sections were cut, deparaffinized and rehydrated by standard techniques before antigen retrieval in EDTA buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD), which consists of Crohn's disease (CD) and ulcerative colitis (UC), is a chronic inflammatory condition that results from dysregulation of the mucosal immune system in the gastrointestinal tract1. The incidence of IBD is increasing, and 1.4 million people in the United States and 2.2 million people in Europe are affected by the disease2.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of these drugs frequently led to multiple adverse events and exhibit limited benefits in long-term disease control (4). SASP is able to cause unwanted effects on male fertility (5) and prolonged or high-dose corticosteroid therapy is associated with hypertension, osteoporosis and immunodeficiency (6).…”
Section: Introductionmentioning
confidence: 99%